2012
DOI: 10.1111/j.1472-765x.2012.03298.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, seasonal occurrence and antimicrobial resistance of Salmonella in poultry retail products in Greece

Abstract: Aims:  To detect the prevalence, the seasonal occurrence and distribution of Salmonella serotypes in poultry products and to determine the resistance profile of Salmonella isolates. Method and Results:  A total of 96 skin‐on chicken carcasses and 30 liver samples were analysed between May 2007 and May 2009 from twenty‐two different commercial farm brands found in retail market countrywide. Salmonella was isolated from 38 (39·5%) of 96 chicken carcasses and from 10 (33·3%) of 30 liver samples. Higher isolation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 31 publications
6
27
4
Order By: Relevance
“…According to our study, multiresistant isolates were 39% (n=88), in line to previous studies in Greece concerning poultry and poultry products [26,27]. Multi-drug resistance is high among isolates from humans in EU (28.9%) with the higher levels reported from Italy (63.1%) and Hungary (55.8%).…”
Section: Discussionsupporting
confidence: 74%
“…According to our study, multiresistant isolates were 39% (n=88), in line to previous studies in Greece concerning poultry and poultry products [26,27]. Multi-drug resistance is high among isolates from humans in EU (28.9%) with the higher levels reported from Italy (63.1%) and Hungary (55.8%).…”
Section: Discussionsupporting
confidence: 74%
“…In this study, high antimicrobial resistance rates were found against nalidixic acid (92.8%), tetracycline (81%), trimethoprim (68.4%), sulfamethoxazole / trimethoprim (61.2%), streptomycin (56.7%), and kanamycin (36.9%). As in the present study, resistance to the above antibiotics have also been frequently reported in a number of other investigations on poultry products in Iran and other countries [12,[18][19][20]28,32,36,[45][46][47][48]. The Salmonella resistance rates to nalidixic acid (92.8%) and tetracycline (81%) found in this study were higher than resistance rates to other antimicrobials because of the overuse of these antimicrobials for treatment and growth promotion in different fields.…”
Section: Resultsmentioning
confidence: 34%
“…However, the survey revealed the contaminations to be minor, although the samples were collected during an outbreak-prone season. Previous studies have revealed that Salmonella contaminations may fluctuate throughout the year because of seasonal effects, and that contaminations are generally relatively higher during summer (Zdragas et al, 2012;Sivaramalingam et al, 2013). Environmental samples reportedly provide an accurate and representative risk indicator for Salmonella contamination in layer flocks and eggs (Namata et al, 2008;Denagamage et al, 2015).…”
Section: Eric-pcr Fingerprinting and Clustering Analysismentioning
confidence: 99%